Why Context Matters in Educational Leadership : a new theoretical understanding - Evers, C. W.; Lakomski, Gabriele (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Why Context Matters in Educational Leadership: A New Theoretical Understanding is unique in the field of educational leadership studies. This book offers a systematic account of educational leadership from the perspective that context matters. It argues that studies of leadership in education can only progress if the importance of context is understood and presents context as a set of constraints under which leadership is exercised. A theoretical book that offers at last three major challenges to dominant positions in the field in a systematic way, it provides a new, coherent, and more realistic way to think about leadership in context. The chapters offer concrete steps for complex problem solving in schools and will help schools tailor solutions to local constraints and circumstances. Written by two leading scholars in the field, this book will be essential reading for students and researchers working in the fields of education, educational administration and leadership"--
Includes bibliographical references and index.
Keywords: Educational leadership; Knowledge, Theory of; Education -- Administration